The Normal Endoscopic Pancreatogram in Koreans - Kang, Jin Kyung (Korean J Intern Med, 1989)
The establishment of endoscopic retrograde cholangiopancreatography (ERCP) as a valuable procedure in diagnostic evaluation of patients with suspected pancreatic disease requires the precise delineation of normal pancreatography. Therefore, to establish normal standards in Koreans of pancreatic ductal morphology, such as course, diameter and length including the shape of the ampulla and the success rate of the ERCP procedure, we analyzed the pancreatograms of persons with proven normal pancreatic status. Of the 449 cases showing normal duodenal papilla, the hemispherical type of shape (49.7%) was the most common, followed by the papillary type (36.5 %) and flat type (13.8%) in order of frequency. The success rate of ERCP procedure (1,020 cases) was 95.3%, and the selective success rate was 90.9% for the panceatic duct and 79.3% for the biliary tree. In the course of the pancreatic duct (286 cases), the ascending type of extension (51.7%) was the most common followed by the sigmoid type (25.2%), horizontal type (22.4%) and descending type (0.7%). The diameter of the pancreatic duct was 3.3 ± 0.8mm in the head, 2.4 ± 0.5mm in the body and 1.5 ± 0.5mm in the tail portion, and there was a tendency that the diameter of the pancreatic duct progressively increased with age. The length of the pancreatic duct was 17.5 ± 2.8cm. In conclusion we hope that, by utilizing these various parameters of the normal endoscopic retrograde pancreatogram, precise diagnosis will be possible.